Elderly migration and natural disasters in the United States from 1960 to 2010 - Boyne, John R., author; Lacy, Michael, advisor; Peek, Lori, advisor; Zahran, Sammy, committee member (Colorado State University. Libraries, 2015)
The United States is a rapidly aging society. As a larger proportion of the population enters into the retirement years, it is likely that a larger portion of the nation's migrants will be elderly. Over the last four decades, natural disasters have also been increasing in frequency and scale across the United States. This thesis draws together two different data sets in order to test the relationship between the two variables, elderly migration and natural disaster loss. The purpose of this thesis is to examine whether migration patterns among the elderly are influenced by natural disaster risk across the country. After a brief introduction, the thesis offers a review of the literature regarding elderly migration in the United States and an exploration of the particular vulnerabilities that the elderly face before, during, and after natural disasters. Then, the thesis reviews the relationship between migration and natural disasters, specifically focusing on climate change, economic development, and amenities. Natural disaster data ranged from 1960 to 2000 and elderly migration data ranged from 1970 to 2010. A fixed effects panel regression model was used to measure the effect natural disaster damage on elderly migration patterns at the county level. The previous decade's disaster damage data was measured against the following decade's elderly migration patterns. The analysis showed statistical significance between several of the variables but little substantive effect between natural disaster damage and elderly migration across the United States measuring across multiple variables of natural disaster data including per capita damage, number of events experienced and number of extreme events experienced. As the elderly continue to comprise a larger proportion of the population and as migration rates continue to rise among this age group, an understanding of the unique relationship between this age group and the risk of natural disasters will help at-risk communities more effectively prepare for extreme events. Although there are limitations to this project, the research contributes to the emerging research field of elderly migration and natural disaster vulnerability.
Keywords: elderly; disasters; migration